An Update on the Exploratory Use of Curcumin in Neuropsychiatric Disorders - Nicolás Lamanna-Rama; Diego Romero-Miguel; Manuel Desco; Maria Luisa Soto-Montenegro (Antioxidants, 2022)
Curcumin is a polyphenol extracted from the rhizome of the turmeric plant. Beyond its common use as a culinary spice in Eastern Asia, curcumin has been proposed as a therapeutic compound due to its antioxidant, anti-inflammatory and neuroprotective properties. Thus, its efficacy has been evaluated in various inflammatory-based psychiatric disorders, such as schizophrenia, depression, or autism. Our aim is to review those preclinical and clinical studies carried out in psychiatric disorders whose therapeutic approach has involved the use of curcumin and, therefore, to discern the possible positive effect of curcumin in these disorders. Preclinical studies and completed clinical trials of curcumin for psychiatric disorders published from January 2005 to October 2021 were identified through searching relevant databases until 31st October 2021. Sixty-five preclinical studies and 15 clinical trials and open-label studies were selected. Results showed a bias toward studies in depression and, to a lesser extent, schizophrenia. In all disorders, the results were positive in reducing psychiatric deficits. Despite the considerable number of beneficial outcomes reported, the small number of trials and the heterogeneity of protocols make it difficult to draw solid conclusions about the real potency of curcumin in psychiatric disorders.